Prevalence of Paternal Prenatal Depression and Its Associated Factors in Saudi Arabia [Corrigendum] - Younis AS; Julaidan GS; Alsuwaylimi RA; Almajed BM; AlShammari RT; AlFirm RB; Alfarra LA (Dove Medical Press, 2024)
Younis AS, Julaidan GS, Alsuwaylimi RA, et al. Risk Manag Healthc Policy. 2024;17:1083–1092. Page 1085, Results, lines 5 and 6, the text “Higher education was attained by more than two-thirds of the fathers (n=335, 69.7%)” should read “Higher education was attained by three-quarters of the fathers (n=335, 75.8%)”. Page 1085, Results, line 6, the text “42.2% of them owned their homes” should read “43.2% of them owned their homes”. Page 1086, Table 1, Expected fetus gender, Male row, the text “179 (40.3)” should read “178 (40.3)”. The authors apologize for these errors.